Robust stabilization of underactuated systems via fast terminal sliding mode - Khan, Qudrat; Bhatti, Aamer Iqbal; Akmeliawati, Rini (2015)
This paper presents a fast terminal sliding mode control strategy for a class of underactuated systems. Strategically, this development encompasses those electro mechanical underactuated systems which can be transformed into the so-called regular form. The novelty of this article lies in the hierarchical development of a fast terminal sliding manifold design for the considered class. Having established sliding mode against the designed manifold, the close loop dynamics becomes finite time stable which results in high precession. In addition, the adverse effects of chattering phenomenon are eliminated and the robustness of the system against uncertainties is confirmed theoretically in a couple of theorems. A comprehensive numerical example of the cart pendulum is presented to verify the claims for the considered class.